2010
DOI: 10.1143/apex.3.031103
|View full text |Cite
|
Sign up to set email alerts
|

High-Quality p-Type ZnO Films Grown by Co-Doping of N and Te on Zn-Face ZnO Substrates

Abstract: This article will report the epitaxial growth of high-quality p-type ZnO layers on Zn-face ZnO substrates by nitrogen and tellurium (N+Te) codoping. ZnO:[N+Te] films show p-type conductivity with a hole concentration of 4 Â 10 16 cm À3 , while ZnO:N shows n-type conduction. The photoluminescence of ZnO:N shows broad bound exciton emission lines. Meanwhile, ZnO:[N+Te] layers show dominant A 0 X emission line at 3.359 eV, with a linewidth as narrow as 1.2 meV. Its X-ray linewidth shows narrower line width of 30 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 32 publications
(18 citation statements)
references
References 14 publications
1
17
0
Order By: Relevance
“…46 Therefore, it is not difficult to understand that sample A is of weak p type. The derived value of the N O -Zn-Te exactly meets the one reported in a prior article, 13 while the one of the N O -Zn-O closely matches the typical activation energy of the substitutional N O in ZnO. 47 The inset of Fig.…”
Section: Resultssupporting
confidence: 86%
“…46 Therefore, it is not difficult to understand that sample A is of weak p type. The derived value of the N O -Zn-Te exactly meets the one reported in a prior article, 13 while the one of the N O -Zn-O closely matches the typical activation energy of the substitutional N O in ZnO. 47 The inset of Fig.…”
Section: Resultssupporting
confidence: 86%
“…At early 2006, Porter et al 19 had explored the properties of ZnO films codoped with Te and N and suggested a feasible route to realize intrinsic, even p-type ZnO. Since then, Park et al 20 and our research team 21 had successively attempted the Te-N codoping in ZnO, and reported the findings of p-type characters measured on the codoped samples. Some possible mechanisms being responsible for the origin of the free hole carriers had also been proposed.…”
Section: Introductionmentioning
confidence: 99%
“…A general breakthrough in this direction has not been achieved up to now. For thin ϐilms, recent attempts to get ZnO p-n junctions and LEDs include ZnO codoped with tellurium and nitrogen [145]. In 2005 the group of Masashi Kawasaki presented the ϐirst p-type ZnO:N/i-ZnO/n-ZnO homojunction thin ϐilm LED [146,147].…”
Section: Light-emitting Diodes and Lasersmentioning
confidence: 99%